Uporaba robotske naprave Lokomat pri ponovnem učenju hoje pri pacientih z okvaro hrbtenjače - Obreza, Pavla (Rehabilitacija (Ljubljana), 2012)
Robot assisted gait training can present an alternative to manual assisted treadmill training. The purpose of this literature review is to find out which variables did researchers investigate in the field of training with the Lokomat system in people with incomplete spinal cord impairments and with what protocols did they measure them. The reviewed articles were retrieved using Medline, Cochrane and Pedro database. The studies either explore the effects of walking on the Lokomat or compare walking on the Lokomat with other rehabilitation strategies. The effect of walking training was evaluated using different protocols. The results have shown reduced heart rate, increase of oxygen consumption and reduced breathing frequency after training with the Lokomat system. Training has caused improvement in muscular coordination and contributed to nerve plasticity in the spinal cord level and higher nerve centres. There is no proof that Lokomat training has a better influence on the rehabilitation outcome in comparison with other methods for relearning walking.
Keywords: hoja; poškodbe hrbtenjače; Robotics; robotika; Spinal cord injuries; Walking